2017
DOI: 10.1007/s10787-017-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of nociceptive pain and inflammatory disorders by total steroid and terpenoid fraction of Euphorbia tirucalli Linn root in experimental in vitro and in vivo model

Abstract: The plant Euphorbia tirucalli Linn has been successfully used as a tribal folk medicine in India and Africa for the management of acute inflammatory, arthritic, nociceptive pain and asthmatic symptoms. The present study was conducted to assess the anti-inflammatory, analgesic, anti-asthmatic and anti-arthritic role of the total steroid and terpenoid rich fractions of the hydro-alcoholic extract of E. tirucalli root (STF-HAETR). STF-HAETR fraction demonstrated 71.25 ± 2.5 and 74.25 ± 5.1% protection against ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Recent reports provide evidence that reactive oxygen species can increase pain processing via TRPV1 (Yoshida et al, 2006; Ibi et al, 2008). It is likely that E. bicolor latex extract is reducing inflammatory mediators and oxidative stress, based on data from other Euphorbia species (Upadhyay et al, 2014; Majid et al, 2015; Palit et al, 2018; Sdayria et al, 2018) as a mechanism underlying the analgesia observed in the present study. This hypothesis is currently under investigation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Recent reports provide evidence that reactive oxygen species can increase pain processing via TRPV1 (Yoshida et al, 2006; Ibi et al, 2008). It is likely that E. bicolor latex extract is reducing inflammatory mediators and oxidative stress, based on data from other Euphorbia species (Upadhyay et al, 2014; Majid et al, 2015; Palit et al, 2018; Sdayria et al, 2018) as a mechanism underlying the analgesia observed in the present study. This hypothesis is currently under investigation.…”
Section: Discussionmentioning
confidence: 56%
“…A number of studies have reported the analgesic and anti-inflammatory properties of different Euphorbia species (Prabha et al, 2008; Gaur et al, 2009; Upadhyay et al, 2014; Majid et al, 2015; Palit et al, 2018; Sdayria et al, 2018). However, no studies have reported the analgesic properties and phytochemical analysis of E. bicolor latex extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A steroid and terpenoid-rich fractions were isolated from the hydroethanolic extract of E. tirucalli root that, at 60 mg/kg, exhibits better protection against peripheral nociceptive pain on acetic acid induced abdominal constrictions mice model than the analgesic aceclofenac sodium and better anti-inflammatory activity in carrageenan-induced mice model than indomethacin [110].…”
Section: Other Biological Activity Of Euphorbia Plantsmentioning
confidence: 99%
“…The anti-arthritic potential of C. album and S. officinale extracts and fractions was evaluated by means of the in vitro protein denaturation assay reported by Palit and colleagues [39] with some modifications.…”
Section: Methodsmentioning
confidence: 99%